The Impact of Extensive Reading Course in EFL Students - Kayla, Aldiva; Sufie Ketaren, Archy; Nuraini, Alfina; Alya Nabilah, Rahmi; Fatwa Mulyati, Yatni (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2024)
The study examines the impact of extensive reading on vocabulary acquisition among EFL students. It presents initial findings based on interviews with nine students, all of whom agreed on the positive effects of extensive reading on improving vocabulary. The research reveals that extensive reading courses usually last about six months, with reading durations varying depending on the genre studied. Common challenges include effective time management and access to reading materials. These results highlight the crucial role of extensive reading in strengthening vocabulary and emphasize the need to customize educational methods to meet the learners' specific needs. The researches highlight the essential function of extensive reading in enhancing vocabulary and stresses the importance of customized educational approaches that address the unique needs of learners. The research provides valuable insights into maximizing vocabulary acquisition through the implementation of extensive reading practices.